2021
DOI: 10.7498/aps.70.20210813
|View full text |Cite
|
Sign up to set email alerts
|

Automatic differentiation and its applications in physics simulation

Abstract: Automatic differentiation is a technology to differentiate a computer program automatically. It is known to many people for its use in machine learning in recent decades. Nowadays, researchers are becoming increasingly aware of its importance in scientific computing, especially in the physics simulation. Differentiating physics simulation can help us solve many important issues in chaos theory, electromagnetism, seismic and oceanographic. Meanwhile, it is also challenging because these applications often requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Thiele-Pfeiffer (1980) described this fossil pollen type as Tricolporopollenites wackersdorfensis. Liu (1985) assigned this pollen type to the form genus Fupingipollenites wackersdorfensis. According to Wang et al (2007), the genus was a warm temperate element growing in humid to semi-arid conditions, probably in riparian and lowland forests, persisting into the Pleistocene in eastern Eurasia (VU3, VU4).…”
Section: Polypodiopsida Spores Of Uncertain Affinitymentioning
confidence: 99%
“…Thiele-Pfeiffer (1980) described this fossil pollen type as Tricolporopollenites wackersdorfensis. Liu (1985) assigned this pollen type to the form genus Fupingipollenites wackersdorfensis. According to Wang et al (2007), the genus was a warm temperate element growing in humid to semi-arid conditions, probably in riparian and lowland forests, persisting into the Pleistocene in eastern Eurasia (VU3, VU4).…”
Section: Polypodiopsida Spores Of Uncertain Affinitymentioning
confidence: 99%
“…In addition, an increasing number of studies in recent years have shown that in ICF, due to the presence of high energy density particles and extreme and violent changes in physical quantities, there are strong nonequilibrium kinetic effects, which are nonnegligible and have an impact on the implosion process. In other fields, nonequilibrium behavioral characteristics induced by flow behaviors such as shock waves are also receiving increasing attention [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%